2016
DOI: 10.1039/c5fo01438g
|View full text |Cite
|
Sign up to set email alerts
|

Plant polyphenols alter a pathway of energy metabolism by inhibiting fecal Bacteroidetes and Firmicutes in vitro

Abstract: The function of plant polyphenols in controlling body weight has been in focus for a long time. The aim of this study was to investigate the effect of plant polyphenols on fecal microbiota utilizing oligosaccharides. Three plant polyphenols, quercetin, catechin and puerarin, were added into liquid media for fermenting for 24 h. The pH values, OD600 of the cultures and the content of carbohydrates at 0, 6, 10, 14, 18 and 24 h were determined. The abundance of Bacteroidetes and Firmicutes in each culture was qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 40 publications
6
47
0
Order By: Relevance
“…PCA and PCoA scores both indicated that gut microbiota in the DMY‐treated group showed a significant structural shift along the first principal component (PC1). Meanwhile, our results showed agreement with many plant polyphenols such as quercetin, anthocyanins, and catechin (Xue et al., ). In order to clarify how DMY reshape gut microbiota composition, the comparisons of the relative abundances at the different levels between the control and DMY‐treated groups were conducted.…”
Section: Resultssupporting
confidence: 88%
“…PCA and PCoA scores both indicated that gut microbiota in the DMY‐treated group showed a significant structural shift along the first principal component (PC1). Meanwhile, our results showed agreement with many plant polyphenols such as quercetin, anthocyanins, and catechin (Xue et al., ). In order to clarify how DMY reshape gut microbiota composition, the comparisons of the relative abundances at the different levels between the control and DMY‐treated groups were conducted.…”
Section: Resultssupporting
confidence: 88%
“…It has been reported that multiple mechanisms are involved in decreasing body weight, such as regulating gut microbiota, inhibiting energy intake and stimulating energy expenditure (Hursel & Westerterp‐Plantenga, ; Xue et al., ). In our study, after 8 wk of being administered a HFD, the levels of TC, TG and LDL‐C were significantly higher in HFD than CONV mice, which is in agreement with the results of Lee et al.…”
Section: Discussionmentioning
confidence: 99%
“…Intact cell walls might significantly limit access of (poly)phenols-catabolising bacteria to their substrates [136], and Mosele et al demonstrated that a simulated duodenal digestion that degraded pectin increased microbial access to many substrates [137]. It has also been demonstrated in vitro that the exposure to (poly)phenols modulates the ability of the microbiota to metabolise fructo-oligosaccharides and to generate short chain fatty acids [138,139]. It must be anticipated that interactions absent from in vitro fermentations are likely in the gastrointestinal tract in vivo.…”
Section: Controls Used In Model Fermentations Have Clearly Demonstratmentioning
confidence: 99%